2022
DOI: 10.3390/nano12050843
|View full text |Cite
|
Sign up to set email alerts
|

Ti3AlC2/Pd Composites for Efficient Hydrogen Production from Alkaline Formaldehyde Solutions

Abstract: Research on catalytic oxidation in a promising but mild manner to remove formaldehyde and produce hydrogen is rarely reported. Here, the use of the Ti3AlC2 MAX phase as support for palladium nanoparticles was explored for the hydrogen generation from alkaline formaldehyde solution at room temperature. The results showed that Ti3AlC2/Pd catalyst with 3 wt% Pd loading had a much higher capability for hydrogen production than conventional Pd nanoparticles. In addition, by further optimizing the formaldehyde conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…11 Liu et al showed that the Ti 3 AlC 2 /Pd catalyst with 3 wt% Pd loading has a much higher capacity for hydrogen production than conventional Pd nanoparticles. 12 MAX phases behave as a support structure for palladium nanoparticles for hydrogen generation from an alkaline formaldehyde solution at room temperature. The layered structures of the MAX phase can also be useful in the hydrogen storage field.…”
Section: Introductionmentioning
confidence: 99%
“…11 Liu et al showed that the Ti 3 AlC 2 /Pd catalyst with 3 wt% Pd loading has a much higher capacity for hydrogen production than conventional Pd nanoparticles. 12 MAX phases behave as a support structure for palladium nanoparticles for hydrogen generation from an alkaline formaldehyde solution at room temperature. The layered structures of the MAX phase can also be useful in the hydrogen storage field.…”
Section: Introductionmentioning
confidence: 99%
“…Liu and coworkers demonstrated that catalytic oxidation and toxic HCHO (formaldehyde) exhibit a higher clean H 2 evolution rate owing to the support of Pd NPs at 3 wt% loadings. Subsequently, enhanced temperature conditions and higher concentrations of analytes indicate best results up to 291.6 mL/min/g (rate of hydrogen synthesis), showing a lower E a (39.48 kJ mol −1 ) than the literature (65 kJ/mol) [117] …”
Section: Nanocomposites For Hydrogen Productionmentioning
confidence: 72%
“…Subsequently, enhanced temperature conditions and higher concentrations of analytes indicate best results up to 291.6 mL/min/g (rate of hydrogen synthesis), showing a lower E a (39.48 kJ mol À 1 ) than the literature (65 kJ/mol). [117] Similarly, Jafarpour and coworkers designed a PdÀ C 3 N 4imine/TiO 2 photocatalyst approachable at visible light to sustain olefin hydrogenation under the nanoscopic class that results in energy alterations. In this work, Pd NPs dispersed over g-C 3 N 4imine-functionalized TiO 2 exhibit superior stability.…”
Section: Materials/ Catalystmentioning
confidence: 99%
“…Although it achieves a relatively higher H 2 production rate of 778 mmol/(g·h), the high price of used catalysts rendered its further application disadvantageous and made it less competitive. Our previous studies also suggested that Pd nanoparticles (NPs) supported on Fe 2 O 3 nanoplate, 3D hierarchical porous carbon, and Ti 3 AlC 2 MAX phase could serve as highly efficient catalysts to produce H 2 from aqueous formaldehyde solution [ 16 , 17 , 18 ]. In addition, Pd NPs supported on metal oxide, such as ZnO nanoroads and TiO 2 nanosheets exposed with (001) facets, realizes efficient H 2 production from formaldehyde solution [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%